Peran Guru PAI Dalam Mengatasi Bullying “Pada Siswa Kelas X di MA Raudlatul Mutaa’allimin” Moropelang Babat Lamongan - ., M. Mukhyiddin; Habibah, Sulhatul; ayu, intan (-, 2025)
Bullying is one of the serious problems that can have a negative impact on students’ psychological and academic development. This study aims to analyze the role of Islamic Religious Education Teachers (PAI) in overcoming bullying in the school environment. The research method used is a qualitative approach with data collection techniques through interviews, observations, and documentation. The subjects of the study are school principals, PAI teachers, and students or students. The results of the study show that PAI teachers have an important role in overcoming bullying through religious and moral approaches. PAI teachers integrate Islamic values in learning, provide advice and guidance, and become role models. In addition, they are active in bullying prevention programs in schools, such as socialization, seminars, and extracurricular activities to increase students’ awareness of the negative impact of bullying and how PAI teachers deal with bullying by calling victims and perpetrators for questioning, providing sanctions according to the perpetrator’s actions, and sending summons letters to the parents of students involved. For cases of bullying that are very outrageous, teachers record the student’s name in the black book.